Sistem Sambungan Momen Tahan Gempa Pada Struktur Baja Bangunan Gedung - Siregar, Andi Saputra; Sitompul, Iskandar Romey; Suryanita, Reni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Based on SNI 1729 2015, there are two concepts in steel structure analysis and design, namely the concept of Load and Resilience Factor Design (LRFD) and Allowable Strength Design (ASD). The design of steel structures has to take into account the safety against earthquake loads according to the 2017 earthquake hazard map which is an update to the previous earthquake map published in 2010. This study aims to obtain the most effective type of steel structure connection in resisting earthquake loads by comparing 3 types of flexural connections between beam and column. The type of connection examined with study were bolted flange plate moment connection and end plate moment connections using stiffeners with four bolts and eight bolts. In this research a 10 floors building with steel structure is modelled. The dimensions of the building are 20 m x 15 m and the height of each story is 3.5 m except for the first story which is 4.5 m. The structure is analyzed by using SAP2000 version 21 software with LRFD and ASD methods. The building is located in the city of Pekanbaru with soft soil conditions. Based on the design result, it was found that the most suitable type of moment connection on the model is end plate moment connection using a stiffener with eight bolts, with a bearing capacity of the end plate of 4403.59 kN. From the structural analysis using the Direct Analysis Method (DAM) it is found that the internal forces in the structure are smaller when using a new earthquake hazard map. Finally, the connection design for this model by using ASD method is about 40% less efficient than by using the LRFD method.Keywords : LRFD, ASD, moment connections, earthquake hazard map 2017